ANALISIS KEMAMPUAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) GURU NORMATIF SMK NEGERI 11 PANDEGLANG - R, Ramdani; Surani, Dewi; Fricticarani, Ade (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
This research aims to analyze the TPACK (Technological Pedagogical Content Knowledge) proficiency of normative teachers in SMK Negeri 11 Pandeglang. Normative teachers need to integrate technology into teaching to make it more effective. The research employs a quantitative descriptive method with a census as the sampling technique. Participants include normative teachers from SMK Negeri 11 Pandeglang. Data were collected through questionnaires and interviews, processed using SPSS 26. The results indicate that the TPACK proficiency of normative teachers is considered good. The average TPACK score is 142.00 with a standard deviation of 15.06, and the majority of teachers fall into the moderate category. TPACK component analysis reveals that teachers possess a solid understanding of technology (TK) and pedagogy (PK), as well as sufficient content knowledge (CK). Their ability to integrate technological content knowledge (TCK), pedagogical content knowledge (PCK), and technological pedagogical knowledge (TPK) is also commendable. There is no significant difference in TPACK between male and female normative teachers, with a Sig. (2-tailed) value of 0.526 > 0.05. This underscores the strong contribution of teachers' knowledge in technology, education, and content to their TPACK proficiency. In the era of technological advancement, these findings emphasize the importance of teachers possessing these skills to deliver effective education.